OPTIMALISASI PENDAMPINGAN STRATEGI DIGITAL MARKETING DAN PENINGKATAN DAYA SAING UMKM JAMUR TIRAM - Lamidi; Marjam Desma Rahadhini; Sisca Dian Rahmawati; Leo Agung Saputra (Dharma: Jurnal Pengabdian Masyarakat, 2025)
Oyster mushrooms is food product that is widely favored by the public. Oyster mushrooms are highly nutritious and provide health benefits. Lack of knowledge on how to develop oyster mushrooms business is an obstacle for MSMEs. The problem faced by partners is not implementing digital marketing to increase oyster mushrooms sales from home industries in Gurung, Dukuh, Banyudono, Boyolali. This service aims to provide on going support to business actors so that they can utilize digital marketing effectively to expand the market, optimizing profits and remain competitive professionally in facing the challenges of the digital era. Digital marketing strategy is a way to increase sales, especially of highquality products because potential buyers access product information more through digital marketing. This service is delivered using a system of socialization, training and mentoring. The first activity carried out socialization and increasing understanding to owners and managers about the value of digital marketing strategy. Second, training in using technology in the form of taking photo and video. Third, mentoring use of social media, choosing the right social media and mentoring in making product photo using digital application and preparing ideas for routine content on optimizing digital marketing. Based on the results of the service, MSMEs interest in digital marketing has increased because it can increase profits and increase public appeal. It is hoped that with a digital marketing strategy. The success of MSMEs can be attributed to the influence of digital markets.